Adição de geomanta e tecido não tecido de polipropileno em cimentos geopoliméricos de pega rápida - Freitas, Sânia Maria Belísio de Andrade (2008)
Geopolymers are cementing materials that depict a number of advantages compared to Portland cement. Contrary to the latter, geopolymers are synthesized at room temperature, thus significantly reducing the emission of CO2 to the atmosphere. Moreover, the composition and synthesis reactions can be tailored to adjust the setting time of the material as well as its compressive mechanical strength. It is then possible to produce geopolymeric cements with short setting times and high compressive strength, although relatively brittle. The objective of the present study was to produce and characterize composite materials by reinforcing fastsetting geopolymeric matrixes with polypropylene geosynthetics (geomats and geotextiles) in an attempt to improve the toughness and tensile strength of the cementing material. Geosynthetics have been increasingly used to reinforce engineering structures, providing higher strength and better toughness. In particular, polypropylene nonwoven and geomats depict other attractive properties such as low density, durability, impact absorption and resistance to abrasion. Fast-setting geopolymers were then synthesized and reinforced with polypropylene nonwoven and geomats. The mechanical strength of the materials, reinforced or not, was characterized. The results showed that relatively short setting times and adequate flowing behavior were achieved by adjusting the composition of the geopolymer. In addition, it is possible to improve the fracture resistance of geopolymeric cements by adding polypropylene geosynthetics. The best results were achieved by reinforcing geopolymer with polypropylene TNT